Manufacturing method of lithium-ion secondary battery
By controlling electrolyte viscosity through a method involving an analytical test piece with a binder resin composition, the adhesive strength and safety of lithium ion secondary batteries are improved, addressing the issues of binder elution and resistance deterioration.
Patent Information
- Application Number
- JP2023518302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-20
- Filing Date
- 2021-11-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-11-22
AI Technical Summary
The adhesive strength between electrodes and separation membranes in lithium secondary batteries is insufficient due to the elution of binder resins like PVDF, leading to increased electrolyte viscosity and potential detachment of inorganic particles, which can cause safety issues and resistance deterioration.
A method to manufacture lithium ion secondary batteries by preparing an analytical test piece with a binder resin composition, immersing it in an organic solvent, and measuring viscosity to select materials that maintain the electrolyte viscosity below a certain level, ensuring the binder resin is less eluted during battery operation.
Prevents the decrease in adhesive strength and resistance increase by maintaining electrolyte viscosity, thereby enhancing the safety and performance of the batteries.
Smart Images

Figure 0007603801000002 
Figure 0007603801000003 
Figure 0007603801000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium secondary battery in which the elution of binder resin during battery operation is small and an increase in the viscosity of the electrolyte is prevented, and a method for manufacturing the same.
[0002] This application claims priority to Korean Patent Application No. 10-2020-0157007, filed on November 20, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Lithium secondary batteries are basically composed of a positive electrode / negative electrode / separator / electrolyte, and are high-energy density energy storage devices that can be charged and discharged while reversibly converting chemical energy and electrical energy, and are widely used in small electronic devices such as mobile phones and notebook PCs. Recently, in response to environmental issues, high crude oil prices, energy efficiency and storage, their application in hybrid electric vehicles (HEVs), plug-in electric vehicles (Plug-in EVs), electric bicycles (E-bikes) and energy storage systems (ESSs) is rapidly expanding.
[0004] In the manufacture and use of such lithium secondary batteries, ensuring the safety of the lithium secondary battery is an important issue to be resolved. In particular, a separator commonly used in lithium secondary batteries exhibits severe thermal shrinkage behavior at high temperatures due to the material properties and manufacturing process properties, which causes safety issues such as internal short circuits. Recently, in order to ensure the safety of lithium secondary batteries, an organic-inorganic composite porous separator has been proposed in which a mixture of inorganic particles and a binder resin is coated on a porous polymer substrate to form a porous coating layer. As the binder resin for such a separator, a PVDF-based polymer is generally used, but there is a high risk that the electrode and the separator will separate from each other due to insufficient adhesive strength between the electrode and the separator, and in such a case, there is a problem that inorganic particles detached from the porous coating layer during the separation process may act as local defects in the lithium secondary battery element. To solve such problems, the introduction of a non-crystalline polymer material such as polyvinylacetate (PVA) has been proposed. However, such amorphous polymer materials have high solubility in the electrolyte, and when the battery is in operation, they dissolve into the electrolyte, reducing the adhesive strength of the separator, which can lead to the detachment of inorganic particles, and the resistance characteristics of the battery can decrease due to an increase in the viscosity of the electrolyte. Therefore, there is a need for a battery design in which the viscosity of the electrolyte can be controlled below a certain level. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been devised to provide a method for manufacturing a battery in which the viscosity of the electrolyte is controlled to a certain level or less during operation of the battery. The method for manufacturing a battery according to the present invention is characterized in that an analytical test piece for a separator is manufactured in advance to confirm the degree of increase in the viscosity of the electrolyte, and the selected material is applied to the manufacture of the battery.
[0006] Other objects and advantages of the present invention will become apparent from the following description and the accompanying drawings, in which: FIG. 1 is a block diagram of a method for manufacturing a semiconductor device according to the present invention; [Means for solving the problem]
[0007] A first aspect of the present invention is a method for manufacturing a battery, the method comprising the steps of: (S1) preparing an analysis specimen including a binder resin composition selected as an analysis target; (S2) immersing the analytical test piece in an organic solvent selected as an analysis target for a predetermined period of time; (S3) removing the analytical test piece from the organic solvent and then measuring the viscosity of the resulting organic solvent; (S4) comparing the viscosity of the organic solvent with a reference value.
[0008] According to a second aspect of the present invention, in the first aspect, the step (S2) is maintained at 23° C. to 28° C. for 24 hours or more.
[0009] According to a third aspect of the present invention, in the first or second aspect, in the step (S2), the analysis test piece is introduced with the binder resin composition in a ratio of 1 wt% to 10 wt% with respect to a total of 100 wt% of the organic solvent and the binder resin composition.
[0010] According to a fourth aspect of the present invention, in any one of the first to third aspects, if the viscosity of the organic solvent in the step (S4) is equal to or lower than a reference value, the binder resin composition to be analyzed and the organic solvent to be analyzed are applied to the manufacture of a battery.
[0011] According to a fifth aspect of the present invention, in the fourth aspect, the reference value is selected from the range of 15 cP to 20 cP.
[0012] According to a sixth aspect of the present invention, in the fifth aspect, the reference value is 17 cP.
[0013] According to a seventh aspect of the present invention, in the fourth aspect, the organic solvent is applied to an electrolyte during the manufacture of a battery.
[0014] According to an eighth aspect of the present invention, in any one of the fourth to seventh aspects, the binder resin composition is used as a binder for a separator during the manufacture of a battery.
[0015] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the analytical test piece is obtained by dissolving the binder resin composition in acetone at a concentration of 1 wt % to 10 wt %, applying the solution to a release film, and drying under humid conditions.
[0016] According to a tenth aspect of the present invention, in the ninth aspect, the humidification conditions have a relative humidity range of 30% to 60%.
[0017] According to an eleventh aspect of the present invention, in any one of the first to tenth aspects, the analytical test piece includes a porous substrate for a separation membrane and a porous coating layer formed on a surface of the porous substrate, the porous coating layer includes inorganic particles and a binder resin, and the binder resin includes the binder resin composition.
[0018] According to a twelfth aspect of the present invention, the method of any one of the first to twelfth aspects further includes the step of manufacturing a separator for a battery by using the binder resin composition as a binder.
[0019] According to a thirteenth aspect of the present invention, in any one of the first to twelfth aspects, the method further includes (S5) preparing an electrode assembly including a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte, wherein the separator includes the selected binder resin composition, and the electrolyte includes the selected organic solvent.
[0020] According to a fourteenth aspect of the present invention, in any one of the first to twelfth aspects, the organic solvent in the step (S2) includes a lithium salt. Effect of the Invention
[0021] By applying a binder resin that is less likely to dissolve in an electrolyte to the production of a battery, the present invention can prevent a decrease in adhesive strength of battery elements and an increase in resistance due to an increase in the viscosity of the electrolyte.
[0022] The following drawings attached to this specification are illustrative of preferred embodiments of the present invention, and are intended to explain the principles of the present invention together with the detailed description, and are not intended to limit the scope of the invention. Note that the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0023] [Figure 1] FIG. 2 is a diagram showing high-temperature charge / discharge and the resulting capacity retention of batteries produced in Examples and Comparative Examples. [Diagram 2] FIG. 2 is a diagram showing room temperature charge / discharge and the resulting capacity retention of batteries manufactured in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiments described in the present specification and the configurations shown in the drawings are merely the most preferable embodiments of the present invention, and do not represent the entire technical idea of the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of filing this application.
[0025] The present invention relates to a method for manufacturing a lithium ion secondary battery, the method comprising the steps of: selecting a binder resin and an organic solvent for an electrolyte solution that are less likely to cause an increase in viscosity of the electrolyte solution due to dissolution of the binder resin, before manufacturing an electrode assembly.
[0026] In one embodiment of the present invention, the selection step includes the following procedure.
[0027] First, an analytical test piece containing a binder resin composition selected as an analysis target is prepared (S1).
[0028] In the present invention, the binder resin composition includes one or more polymeric materials, i.e., one polymeric material or a combination of two or more polymeric materials, and the polymeric material is not particularly limited as long as it can be used as a binder for a battery. That is, the polymeric material may be one or more selected from a candidate group that can be used as a binder for manufacturing a lithium ion secondary battery. For example, the binder resin composition may include only one polymeric material, or two or more different polymeric materials. In addition, when the binder resin composition includes two or more polymeric materials, the content ratio of these is not limited to a specific resin, and may have various values depending on the experimental design. That is, since the present invention is to find an optimal combination of polymeric materials that can be used as a binder, the type and content ratio of the polymeric materials to be analyzed are not limited to a specific range.
[0029] Examples of the polymeric material include PVDF-based binder resins, such as polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polyvinylidene fluoride-trichloroethylene; (meth)acrylic polymer resins such as polymethylmethacrylate, polyethylhexyl acrylate, and polybutylacrylate; polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate (PVA), ethylene-vinyl acetate copolymer (polyethylene-co-vinyl acetate), polyethylene oxide, polyarylate, cellulose acetate, and cellulose acetate butyrate. Examples of suitable materials include cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxyl methyl cellulose, and one or more of these may be selected and used to prepare an analytical test piece. However, the present invention is not limited to these. In addition to the above components, any polymer material that can be used as a binder during battery manufacturing may be used as an analytical subject without any limitations.
[0030] In one embodiment of the present invention, the analytical test piece may be prepared in the form of a separator for a lithium ion secondary battery or an electrode for a lithium ion secondary battery. When the analytical test piece is provided in the form of a separator or an electrode for a lithium ion secondary battery, an environment similar to that of an actual battery can be created, and thus the reliability of the analytical results can be improved. In yet another embodiment, the analytical test piece may be prepared in the form of a polymer film prepared by forming a binder resin composition into a sheet-like film. When prepared in the form of a polymer film, the time required for the analysis process can be shortened.
[0031] In one embodiment of the present invention, when the analysis specimen is prepared in the form of a polymer film, the analysis specimen may be prepared by melting and extruding the binder resin composition to be analyzed at a high temperature to form a film. Alternatively, the analysis specimen may be prepared by dissolving the binder resin composition to be analyzed in an organic solvent to prepare a polymer solution, applying the polymer solution to a release film, and drying the solution to remove the solvent. The organic solvent is not particularly limited as long as it dissolves the binder resin composition and is easy to dry. For example, the organic solvent may include one or more selected from acetone, toluene, cyclohexanone, cyclopentane, tetrahydrofuran, cyclohexane, xylene, and N-methylpyrrolidone.
[0032] Meanwhile, in one embodiment of the present invention, the drying is not particularly limited as long as it is a common drying method, and an appropriate method such as natural drying, air drying, heat drying, etc. can be selected and applied. Alternatively, the drying can be performed under humidified conditions with a relative humidity of 30% to 60%, depending on the polymer material used.
[0033] Meanwhile, in one embodiment of the present invention, when the analytical test piece has the form of a separation membrane, the separation membrane may have the following structural features.
[0034] The separator includes a porous polymer substrate and a porous coating layer coated on at least one surface of the porous polymer substrate and containing a binder and inorganic particles. The binder adheres the inorganic particles to each other so that they are bonded to each other, and the inorganic particles and the porous polymer substrate are bonded to each other so that they are bonded to each other. The inorganic particles are in substantial contact with each other to form interstitial volumes, and the interstitial volumes between the inorganic particles become vacant spaces to form pores in the porous coating layer.
[0035] In a specific embodiment of the present invention, the porous polymer substrate can be used without any particular limitation as long as it can electrically insulate the negative electrode and the positive electrode to prevent short circuiting and provide a path for lithium ions to move, and can be used as a separator material for lithium secondary batteries in general. Examples of such porous polymer substrates include porous films and nonwoven fabrics containing polymer materials. In addition, the polymer material may include at least one selected from polyolefin polymers including polyethylene and / or polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.
[0036] The porous coating layer according to the present invention is formed in a layer on one or both sides of the porous polymer substrate. The porous coating layer includes a mixture of a plurality of inorganic particles and a binder, and the inorganic particles are accumulated through the binder to form a layer. The binder of the porous coating layer adheres the inorganic particles to each other (i.e., the binder connects and fixes the inorganic particles) so that the inorganic particles are maintained in a bound state, and the inorganic particles and the porous polymer substrate can be maintained in a bound state by the binder. The inorganic particles of the porous coating layer can form an interstitial volume in a state where they are substantially in contact with each other, and the interstitial volume means a space limited by inorganic particles that are substantially in contact in a packed structure (closed packed or densely packed) of the inorganic particles. The interstitial volume between the inorganic particles can become an empty space to form pores of the porous coating layer.
[0037] The composition ratio of the inorganic particles and the binder resin constituting the porous coating layer may be determined in consideration of the thickness, pore size and porosity of the finally manufactured porous coating layer of the present invention. In a specific embodiment of the present invention, the composition ratio of the inorganic particles and the binder may be 50 to 99.9 wt % or 60 to 99.5 wt % of the inorganic particles and 0.1 to 50 wt % or 0.5 to 40 wt % of the binder, based on weight.
[0038] Meanwhile, the diameter D50 and / or type of the inorganic particles are not particularly limited, and the inorganic particles to be applied during the manufacture of an actual battery may be used to prepare an analytical test piece. For example, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles are not particularly limited as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the applied electrochemical element (e.g., 0 to 5 V based on Li / Li+). Examples of the inorganic particles include SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, γ-AlOOH, SiC, TiO2, etc., and one or a mixture of two or more selected from these may be used.
[0039] The separation membrane analytical test strip may be prepared in accordance with a method for preparing a separation membrane to be actually produced. In a specific embodiment of the present invention, the separation membrane analytical test strip may be prepared in the following manner.
[0040] First, a suitable organic solvent is prepared, and then inorganic particles and a binder are mixed therein to prepare a slurry composition for forming a porous coating layer, which is then applied to at least one surface of a porous polymer substrate and dried to form a porous coating layer. The organic solvent is not particularly limited as long as it can dissolve the binder and uniformly disperse the inorganic particles. As these solvents, solvents with low boiling points and high volatility are preferred because they can be removed in a short time and at low temperatures. Specific examples include acetone, toluene, cyclohexanone, cyclopentane, tetrahydrofuran, cyclohexane, xylene, or N-methylpyrrolidone, or a mixture thereof. Preferably, a solvent that is actually used in the manufacture of a separation membrane can be used.
[0041] Meanwhile, in a specific embodiment of the present invention, the coating and drying of the slurry composition may be performed by a phase separation phenomenon caused by a non-solvent. The phase separation may be performed by a wet phase separation method or a immersion phase separation method. The wet phase separation method refers to a method in which a non-solvent for phase separation is introduced in a gaseous state, and the immersion phase separation method refers to a method in which the resultant product coated with the slurry composition is immersed in a coagulation liquid containing a non-solvent for a predetermined time. The non-solvent is not particularly limited as long as it does not dissolve the binder resin and is partially compatible with the solvent. For example, it may be one or more selected from the group consisting of water, methanol, ethanol, isopropanol, and butanol.
[0042] The method for manufacturing the analytical test strip is described as an example of various methods, and is not particularly limited to the above method. In the present invention, the analytical test strip may be manufactured using a manufacturing method actually used for manufacturing batteries.
[0043] When the analytical test piece is prepared as described above, the analytical test piece is immersed in an organic solvent selected as an analysis target and maintained for 24 hours or more (S2).
[0044] In one embodiment of the present invention, the temperature of the organic solvent is preferably maintained at 23°C to 28°C. For example, the temperature of the organic solvent may be maintained at about 25°C while the analytical test piece is immersed. In one embodiment of the present invention, the organic solvent may be, but is not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, ethyl methyl carbonate (EMC), γ-butyrolactone, fluorine-substituted carbonate, or a mixture thereof. In one embodiment of the present invention, the organic solvent may be one or more selected from a candidate group considered as usable in the manufacture of an actual battery and introduced into the S2 step.
[0045] Meanwhile, in one embodiment of the present invention, in S2, the analysis test piece may be added with a binder resin composition (polymer material) content of 1 wt% to 10 wt% relative to a total of 100 wt% of the organic solvent and the binder resin composition (polymer material). For example, the analysis test piece may be added with a polymer material content of 3 wt% to 8 wt%, for example, about 5 wt%, relative to a total of 100 wt% of the organic solvent and the polymer material. However, this is not limited thereto, and can be appropriately adjusted in consideration of the amount of binder resin contained in the total of the binder resin and the electrolyte during actual battery manufacturing.
[0046] Meanwhile, in one embodiment of the present invention, the organic solvent may further contain a lithium salt in the range of 0.5 M to 1.5 M. By adding the lithium salt in this way, an environment close to an actual electrolyte solution can be created. The lithium salt is A + B - A + Li + , Na + , K + or a combination thereof, such as B - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a combination thereof. The lithium salt is not particularly limited to the above components. In one embodiment of the present invention, the lithium salt may be selected from a variety of combinations in consideration of actual use.
[0047] In one embodiment of the present invention, the analysis method can be used to select a polymeric material for a certain organic solvent, or can be used to select an organic solvent for a certain polymeric material, or, in order to ensure evaluation results for various combinations of organic solvents and polymeric materials, the combinations can be different for each experiment, and the analysis method can be performed on the combinations.
[0048] Next, the analytical test piece is removed from the organic solvent, and the viscosity of the organic solvent is measured and compared with a reference value (S4). The organic solvent contains the binder resin contained in the analytical test piece and has an increased viscosity due to the dissolution of the binder resin compared to before the analytical test piece was immersed.
[0049] The viscosity can be measured by any method, including any ordinary viscometer, but in this specification, the viscosity is preferably measured at 25° C. using a DV-E VISCOMETER (BROOKFIELD), with a single spindle and at 100 rpm for 60 seconds. * Viscometer: DV-E VISCOMETER, BROOKFIELD * Viscosity measurement conditions: 25°C, #1 spindle, 30 rpm, 60 seconds *Viscosity unit: cP
[0050] Meanwhile, the reference value of the viscosity in the step (S4) may be a value suitable for battery operation, and may be obtained inductively through experiments, and may be preferably selected in the range of 15 cP to 20 cP. In a specific embodiment of the present invention, the reference value in the step (S4) may be 17 cP. When the viscosity of the organic solvent is 17 cP or less, the polymer material used in the analytical test piece, or the polymer material used in the analytical test piece and the organic solvent used in the analytical test piece are applied to the manufacture of a battery. In this specification, applying the polymer material used in the analytical test piece to the manufacture of a battery means that the same material as the binder resin composition (polymer material) used in the analytical test piece is applied to the manufacture of a battery, and does not mean that the one treated as the analysis subject is used. In this specification, applying the organic solvent used in the analysis to the manufacture of a battery means that a material having the same components as the organic solvent used in the analysis is applied to the manufacture of a battery, and does not mean that the one directly used in the analysis is used. That is, it does not mean that the result obtained after removing the analytical test piece in (S4) is directly used as an electrolyte.
[0051] In one embodiment of the present invention, when the viscosity of the organic solvent measured in step (S4) is 17 cP or less, the polymer material may be used as a separator binder and / or an electrode binder, and the organic solvent may be used as an electrolyte organic solvent when manufacturing a battery. For example, the separator binder when manufacturing a battery may consist only of the polymer material used in manufacturing the analytical test strip. In addition, the electrolyte when manufacturing a battery may consist only of the organic solvent components used in the analysis.
[0052] If the viscosity measured using the analytical test piece exceeds 17 cP, even if the elution rate of the binder resin composition (polymer material) used is high or the amount of elution is small, the viscosity of the organic solvent may increase excessively due to the eluted components. On the other hand, if the viscosity measured using the analytical test piece is 17 cP or less, even if the elution rate of the binder resin composition (polymer material) is low or the amount of elution is large, it may not affect the increase in the viscosity of the organic solvent. Therefore, when a polymer material and / or an organic solvent having a value of 17 cP or less is applied to the manufacture of a battery, the elution of the binder resin into the electrolyte is prevented, and the level of binding force to be achieved by the binder can be maintained. As a result, the detachment of inorganic particles can be prevented, and the adhesive force between the electrode and the separator can be maintained for a long period of time. In addition, the viscosity of the organic solvent does not increase and is maintained at an appropriate level, so that the problem of battery performance deterioration due to increased resistance does not occur.
[0053] Although the present specification has been mainly described with respect to the application of a selected binder resin composition to a separator, the selected binder resin composition may be applied to a separator, or to an electrode, or to both a separator and an electrode.
[0054] In one embodiment of the present invention, the separation membrane may refer to the description of the analytical test piece. In particular, when a binder is used in the separation membrane, the binder may include a binder resin composition selected based on the above description. Preferably, the binder may consist of only the selected binder resin composition.
[0055] In one embodiment of the present invention, the electrode is an electrode for a lithium ion secondary battery, and may be a positive electrode and / or a negative electrode.
[0056] In a specific embodiment of the present invention, the negative electrode may include a current collector and a negative electrode active material layer formed on the surface of the current collector. According to a specific embodiment of the present invention, the negative electrode is manufactured by applying and drying a negative electrode active material on the current collector, and may further include a binder and a conductive material as required.
[0057] In one embodiment of the present invention, the negative electrode active material layer includes a negative electrode active material, a negative electrode binder, and a conductive material.
[0058] The components of the negative electrode active material are not particularly limited as long as they are used in the field of secondary batteries. For example, the negative electrode active material may include a carbon-based material. The carbon-based material may be one or more selected from the group consisting of crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low-crystalline soft carbon, carbon black, acetylene black, graphene, and fibrous carbon. Desirably, the negative electrode active material may include crystalline artificial graphite and / or crystalline natural graphite. Furthermore, any substance that can be used as a negative electrode active material in a secondary battery can be used. For example, the negative electrode active material may be lithium metal; Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. may be further included, one or more selected from these.
[0059] Meanwhile, in a specific embodiment of the present invention, the positive electrode may include a current collector and a positive electrode active material layer formed on a surface of the current collector. According to a specific embodiment of the present invention, the positive electrode may be manufactured by coating and drying a positive electrode active material on the positive electrode current collector, and may further include a binder and a conductive material as necessary.
[0060] The positive electrode active material is not particularly limited in terms of its components, so long as it is used in the field of secondary batteries. For example, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, LiNiMnCoO2, and LiNi 1-x-y-z Co x M1 y M2 z O2 (M1 and M2 are each independently any one selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg, and Mo, and x, y, and z are each independently atomic fractions of oxide composition elements, and are 0≦x<0.5, 0≦y<0.5, 0≦z<0.5, and x+y+z≦1.) or a mixture of two or more thereof.
[0061] The current collector is generally made to a thickness of 3 to 500 μm. There are no particular limitations on the current collector, so long as it does not induce chemical changes in the battery and has high conductivity. For example, stainless steel, copper, aluminum, nickel, titanium, or those whose surfaces are surface-treated with carbon, nickel, titanium, silver, etc. may be used.
[0062] Meanwhile, the binder included in the electrode may include a binder resin composition selected according to the above content, and preferably, the binder may consist of only the selected binder resin composition.
[0063] In this way, the present invention identifies and selects a binder resin for a separator and / or an electrode and an organic solvent for an electrolyte that do not increase the viscosity of the electrolyte before manufacturing a battery, and applies them to the manufacture of a battery, thereby manufacturing a battery with excellent electrochemical properties.
[0064] Working Example (1) Selection of binder resin composition and organic solvent The binder resin composition was dissolved in acetone at 5 wt%, and then applied to a PET film and dried under a condition of relative humidity of 45% to prepare a binder film. An organic solvent was prepared by mixing ethyl carbonate and ethyl methyl carbonate in a volume ratio (vol%) of 3:7. The binder film was immersed in the organic solvent and maintained at 25°C for 24 hours. The binder film was then removed from the organic solvent to obtain an organic solvent. The organic solvent was filtered using a 300 mesh sieve. The viscosity of the final analytical test piece was measured using a Viscometer TV-22 (TOKI Sangyo Co., Ltd.). The measurement conditions were 25°C and 100 rpm. The types of binder resin compositions used in each example and comparative example and the viscosity measurement results are shown in Table 1 below.
[0065] [Table 1]
[0066] (2) Battery manufacturing 1) Separation membrane production As inorganic particles, Al2O3 powder having a D50 diameter of 500 nm was prepared, and as binders, the same as those shown in Table 1 were prepared. The Al2O3 powder and binder were prepared in a weight ratio of 80:20. The binder was dissolved in acetone as a solvent at 60°C for about 5 hours to prepare a binder solution. Then, the inorganic particles were added to the binder solution. The binder solution containing the inorganic particles was passed through a layer of beads having a diameter of 0.65 mm 3 to 5 times using a bead mill to disperse the inorganic particles, thereby preparing a composition for forming a porous coating layer. In this case, the solid content in the composition for forming a porous coating layer was adjusted to 25 wt%.
[0067] As a porous polymer substrate, a polyethylene porous polymer film having a size of 6 cm×15 cm (thickness: 9 μm, porosity: 43%, ventilation time: 110 seconds, resistance: 0.45 Ω) was prepared.
[0068] The composition for forming a porous coating layer was applied to both sides of the polyethylene porous polymer substrate having a size of 6 cm x 15 cm by dip coating. Then, the polyethylene porous polymer substrate coated with the composition for forming a porous coating layer was maintained under a relative humidity of 40% to perform humidification phase separation, thereby preparing a separator for a lithium secondary battery having a porous coating layer in which a binder and inorganic particles are mixed on both sides of the porous polymer substrate. In the porous coating layer, the binder adheres the inorganic particles to each other so as to maintain a state in which the inorganic particles are fixed to each other, and adheres the inorganic particles to the porous polymer substrate so as to maintain a state in which the inorganic particles are fixed to each other, and the inorganic particles form interstitial volumes in a state in which the inorganic particles are in contact with each other, and the interstitial volumes between the inorganic particles become vacant spaces to form pores in the porous coating layer. In addition, the binder layer has a structure in which porous pores generated when the solvent is exchanged with water as a non-solvent are also formed. The total coating amount of the applied porous coating layer was 5.8 g / m 2 In this manner, separation membranes (Example 1-1, Example 2-1, Comparative Example 1-1, Comparative Example 2-1, and Comparative Example 3-1) were prepared. Example 1-1 used the binder resin of Example 1, Example 2-1 used the binder resin of Example 2, Comparative Example 1-1 used the binder resin of Comparative Example 1, Comparative Example 2-1 used the binder resin of Comparative Example 2, and Comparative Example 3-1 used the binder resin of Comparative Example 3.
[0069] 2) Battery manufacturing The negative electrode slurry was prepared by mixing artificial graphite as the negative electrode active material, denka black (carbon black) as the conductive material, and polyvinylidene fluoride (PVdF) as the binder in a weight ratio of 75:5:25, and adding N-methylpyrrolidone (NMP) as a solvent. 2The negative electrode was prepared by coating the negative electrode active material on a copper current collector in a loading amount of 1000g and drying the coated copper current collector.
[0070] A positive electrode slurry was prepared by adding LiCoO2 as a positive electrode active material, denka black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder to N-methylpyrrolidone (NMP) as a solvent in a weight ratio of 85:5:15. The positive electrode active material slurry was coated on a sheet-shaped aluminum current collector and dried, and the final positive electrode loading was 3.3 mAh / cm. 2 The positive electrode active material layer was formed so as to have the following structure.
[0071] The separator was interposed between the negative and positive electrodes prepared as above, and a non-aqueous electrolyte (1M LiPF6, ethyl carbonate and ethyl methyl carbonate mixed in a volume ratio (vol%) of 3:7) was injected to prepare a coin cell. In this manner, batteries (Example 1-2, Example 2-2, Comparative Example 1-2, Comparative Example 2-2, and Comparative Example 3-2) were prepared. Example 1-2 used the separator of Example 1-1, Example 2-2 used the separator of Example 2-1, Comparative Example 1-2 used the separator of Comparative Example 1-1, Comparative Example 2-2 used the separator of Comparative Example 2-1, and Comparative Example 3-2 used the separator of Comparative Example 3-1.
[0072] (3) Evaluation experiment data 1) High temperature cycle test The batteries of Example 1-2, Comparative Example 1-2, and Comparative Example 2-2 were charged and discharged 400 times at 45° C., and the results are shown in FIG. 1. Charging was performed in CC / C mode at 1C to 4.25V with a 0.05C cut-off condition. Discharging was performed in CC mode at 1C to 3.0V. Referring to FIG. 1, it can be seen that the battery of Example 1-2 is superior in terms of capacity retention rate compared to the batteries of Comparative Example 1-2 and Comparative Example 2-2.
[0073] 2) Room temperature cycle test The batteries prepared in Examples 1-2, 2-2, and Comparative Example 3-2 were repeatedly charged and discharged 400 times at 25° C., and the results are shown in FIG. 2. The batteries were charged in CC / CV mode at 1C to 4.25V, with a 0.05C cutoff condition. The batteries were discharged in CC mode at 1C to 3.0V. Referring to FIG. 2, it can be seen that the batteries of the Examples have a better capacity retention rate than the battery of Comparative Example 3-2. In particular, the viscosity of Example 2-2 was measured at 17cp, and it was confirmed that the battery had a capacity retention rate similar to that of Example 1-2. Meanwhile, the battery of Comparative Example 3-2 had a small difference in viscosity from Example 2-2, but the battery of Comparative Example 2-2 had a significantly lower capacity retention rate than the battery of Comparative Example 2-2.
Claims
1. (S1) preparing an analysis specimen including a binder resin composition selected as an analysis target; (S2) immersing the analytical test piece in an organic solvent selected as an analysis target for a predetermined period of time; (S3) removing the analytical test piece from the organic solvent and then measuring the viscosity of the resulting organic solvent; (S4) comparing the viscosity of the organic solvent with a reference value; (S5) preparing an electrode assembly including a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte; Including, The step (S2) is to maintain the temperature at 23°C to 28°C for 24 hours or more; In the step (S2), the binder resin composition is added to the analysis specimen in a ratio of 1 wt % to 10 wt % based on a total of 100 wt % of the organic solvent and the binder resin composition, If the viscosity of the organic solvent in the step (S4) is equal to or less than a reference value, the binder resin composition to be analyzed and the organic solvent to be analyzed are applied to the manufacture of a battery; The reference value is selected from the range of 15 cP to 20 cP, The organic solvent is used as an organic solvent for an electrolyte in the production of a battery, The binder resin composition is used as a binder for a separator and / or a binder for an electrode in the manufacture of a battery. A method for manufacturing a lithium-ion secondary battery.
2. The method for producing a lithium ion secondary battery according to claim 1 , wherein the reference value is 17 cP.
3. 3. The method for producing a lithium ion secondary battery according to claim 1, wherein the analysis test piece is obtained by dissolving the binder resin composition in acetone at 1 wt % to 10 wt %, applying the solution to a release film, and drying the solution under humid conditions.
4. The method for producing a lithium ion secondary battery according to claim 3, wherein the humidification condition has a relative humidity in the range of 30% to 60%.
5. 5. The method for producing a lithium ion secondary battery according to claim 1, wherein the analytical test piece comprises a porous substrate for a separation membrane and a porous coating layer formed on a surface of the porous substrate, the porous coating layer comprises inorganic particles and a binder resin, and the binder resin comprises the binder resin composition.
6. The method for manufacturing a lithium ion secondary battery according to claim 1 , further comprising the step of manufacturing a separator for a battery by applying the binder resin composition as a binder.
7. A method for manufacturing a lithium ion secondary battery described in any one of claims 1 to 6, wherein the separation membrane contains the selected binder resin composition and the electrolyte solution contains the selected organic solvent.
8. The method for preparing a lithium ion secondary battery according to claim 1 , wherein the organic solvent in the step (S2) contains a lithium salt.
Citation Information
Patent Citations
Separator for electronic component, and electronic component
JP2005019157A
Lithium-ion rechargeable battery
JP2012510704A
Separator for electrochemical device including low-resistance coating layer and method for manufacturing same
JP2020532845A
A secondary battery
KR1020150044637A
Binder composition for secondary battery, anode including the binder composition, and lithium battery including the anode
US20140239239A1
